Role and Access Based data Segregator for Security of Big Data. (2016) - Gupta, Aayush; Pandhi, Ketan; Bindu, P.V.; Thilagam, P. Santhi
Abstract: A conceptual storage model based on Hadoop is proposed in order to solve the security problems such as transmission, data storage, and data verification in distributed networks. The model is meant for private cloud of an organization and allows the organization to store data ranging from confidential to public on the same cloud. The proposed model for cloud storage segregates data based on roles in the hierarchy of the organization having access to the data. In addition, it takes into account how valuable the data is for the organization and number of times the data has been accessed within a certain period of time. The model is a combination of Role Based Access Control and Hadoop Distributed File System, and employs a normalization technique to utilize the resources efficiently by evenly distributing data over different servers.